2022
DOI: 10.3389/fvets.2022.948929
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of lncRNA in the skeletal muscle of rabbits at different developmental stages

Abstract: It is universally acknowledged that lncRNA plays an important role in the regulation of animal skeletal muscle development regulation. However, there is a lack of relevant research on lncRNA in rabbit skeletal muscle development. Thus, we explored the expression profiles of lncRNA in rabbits at three growth stages (2-week-old fetus, 6-week-old post-weaning, and 6-month-old adult) using RNA-seq. A total of 554 differentially expressed lncRNAs (235 up- and 319 down-regulated) were found between the post-weaning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…This study found that the expression of CDKN1A was significantly increased at 2 days of age, suggesting that CDKN1A could promote muscle fiber transformation. After birth, muscle development is mainly dependent on muscle fiber hypertrophy, which is limited by inadequate oxygen supply [9]. Glycolysis plays essential role in stabilizing ATP synthesis and provides energy for muscle contraction and exercise [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study found that the expression of CDKN1A was significantly increased at 2 days of age, suggesting that CDKN1A could promote muscle fiber transformation. After birth, muscle development is mainly dependent on muscle fiber hypertrophy, which is limited by inadequate oxygen supply [9]. Glycolysis plays essential role in stabilizing ATP synthesis and provides energy for muscle contraction and exercise [32].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the diameter of myofibers reached its maximum at 150 days and identified six genes involved in the development of skeletal muscle fibers, including MSTN (Myostatin) and MYF6 (myogenic factor 6), through the analysis of the whole transcript sequence of the longissimus dorsi muscle of Ningxiang pigs at four different stages of postnatal life (Yu et al, 2023) [8]. It has been shown that using RNA-Seq to analyze the expression profiles of lncRNAs in three developmental stages of skeletal muscle in New Zealand rabbits and identified lncRNAs such as LINC-8613 and LINC-8705, which are involved in the proliferation and energy metabolism of skeletal muscle cells [9]. The whole transcriptome RNA-Seq analysis of goat dorsal muscles at four stages of prenatal and postnatal development have revealed that biological pathways such as Rap1 signaling pathway, PI3K-Akt signaling pathway, and AMPK signaling pathway are directly related to temporal changes of skeletal muscle development in goats [10].…”
Section: Introductionmentioning
confidence: 99%